The moderating effects of self-efficacy on the relationship between stress and cigarette smoking behavior among adolescents in Kerman, Iran - Golestan, Samira; Abdullah, Haslinda (Canadian Center of Science and Education, 2015)
This paper aims to examine the relationship between the individual factor of stress and cigarette smoking behavior and also determine the moderating effect of self-efficacy on the relationship between stress and cigarette smoking behavior among adolescents in Kerman, Iran. A quantitative research method was employed. The samples included three hundred current smoker adolescents between the ages of 15 to 18. The data were collected by means of self-administered questionnaires and then analyzed by AMOS software. The direct structural model was employed to determine the path relationships between the individual factor of stress and cigarette smoking behavior. In addition, a multi-group analysis approach was applied to assess the moderating effect of self-efficacy on the relationship between stress and cigarette smoking behavior among adolescents. The results of testing the structural equation model revealed that there is a positive significant relationship between the individual factor of stress and cigarette smoking behavior. It was also found that self-efficacy significantly moderates the effects of stress on the cigarette smoking behavior among adolescents. The paper proposes some suggestions in order to prevent cigarette smoking behavior among adolescents.